Using phage display technology to obtain Crybodies active against non-target insects. Issue 1 (December 2017) - Domínguez-Flores, Tania; Romero-Bosquet, María; Gantiva-Díaz, Diana; Luque-Navas, María; Berry, Colin; Osuna, Antonio; Vílchez, Susana
Abstract The insecticidal Cry toxins produced byBacillus thuringiensis (Bt) are increasingly important in the biological control of insect pests and vectors of human disease. Markets for Bt products and transgenic plants expressing their toxins are driven by their specificity, safety and the move away from chemical control agents. However, the high specificity of Cry toxins can also prove to be a limitation when there is no known Cry toxin active against a particular target. Novel activities can be discovered by screening natural Bt isolates or through modifications of the Cry proteins. Here we demonstrate the use of λ-phage displaying Cry1Aa13 toxin variants modified in domain II loop 2 (Crybodies) to select retargeted toxins. Through biopanning using gut tissue from larvae of the non-target insectAedes aegypti, we isolated a number of phage for further testing. Two of the overexpressed Cry toxin variants showed significant activity againstA .aegypti larvae while another induced mortality at the pupal stage. We present the first report of the use of phage display to identify novel activities toward insects from distant taxonomic Orders and establish this technology based on the use of Crybodies as a powerful tool for developing tailor-made insecticides against new target insects.